Impact of Digital Payment on Business Performance: A Study of Street Vendors in Odisha. Issue 2 (June 2022) - Panda, Shradhanjali; Sahoo, Ansuman
A paradigm shift in the Indian banking sector coping with the technological transformation has led to a sharp rise in digital payments and receipts. The nation is witnessing a significant growth rate of around 30% (Kumari, 2020 ) in digital payment, and receipts helping the economy move towards a cashless era. In this study, street vendors are considered. This article aims to examine the level of digital payment awareness among street vendors and its impact on their business performance. To work on this purpose, data are collected from three tier 2 cities, that is, Cuttack, Khurda and Berhampur in Odisha using both structured questionnaires and the interview method. Furthermore, this empirical study incorporates both primary and secondary data in order to provide an appropriate response to the above-mentioned goal. Collected data are analysed using statistical measures, such as gap study, principal component analysis, ANOVA and regression method. Findings of the study reveal street vendors are a financially excluded segment of the economy. An in-depth analysis of the result shows there is a strong association between the identified aspects of digital payment awareness and business performance of street vendors. The paper concludes by citing the managerial implication of its findings.